Sistem Peringatan Dini Bencana Banjir Berbasis IoT dengan Platform Firebase - Pamungkas, Tri Dedi; Fitrizawati, Fitrizawati (Proceedings Series on Physical & Formal Sciences, 2023)
The firebase platform is one of the Io-T services created by google. This platform uses real-time internet-based communication. In principle, data is stored in one database and can be read by several devices simultaneously with certain conditions. Flood is a disaster that generally affects certain areas or areas caused by the overflow of river water that passes through the area. By reading the condition of the river water level at the overflow point for that area, the data can be used as a reference as a warning for potentially affected areas. Ultrasonic sensor with esp8266 microprocessor can be used as a data collector, and by applying the calculation of the speed of level change over time it can provide an estimate of the potential for flooding and the time. The data sent from this sensor is sent to the database as the main data. Every area that might be affected is installed with an esp8266 microprocessor and an audio player module as a warning of the possibility of a flood disaster. The microprocessor installed in this area is given access to read the main data continuously so that it can provide accurate information as quickly as possible.